2023
DOI: 10.1038/s41598-023-49902-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators drive neuroinflammation in autism spectrum disorder and cerebral palsy

Uyen Thi Trang Than,
Liem Thanh Nguyen,
Phuong Hoang Nguyen
et al.

Abstract: Inflammation conditions are associated with autism spectrum disorder (ASD) and cerebral palsy (CP), primarily observed in the peripheral immune system. However, the extent of neuro-inflammation and neuro-immune dysregulation remains poorly studied. In this study, we analyzed the composition of cerebrospinal fluid (CSF) to uncover the inflammatory mediators driving the neuro-immune system in ASD and CP patients. Our findings revealed that ASD patients had elevated levels of four inflammatory cytokines (TNF-α, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, this study reported no significant correlation between the level of TNF-α in serum and CSF, and the use of small sample sizes may be responsible for non-conclusive tests. Presence of neuroinflammation is further supported by a recent study that found elevated levels of TNF-α and interleukins (Than et al, 2023) in ASD.…”
Section: Methodsmentioning
confidence: 65%
“…However, this study reported no significant correlation between the level of TNF-α in serum and CSF, and the use of small sample sizes may be responsible for non-conclusive tests. Presence of neuroinflammation is further supported by a recent study that found elevated levels of TNF-α and interleukins (Than et al, 2023) in ASD.…”
Section: Methodsmentioning
confidence: 65%
“…Furthermore, our study emphasizes the connection between IL-17 A, a pro-inflammatory cytokine, and the severity of ASD. Dysregulated cytokine levels, indicative of immune system dysfunction and potential neuroinflammation, have been reported in individuals with ASD [ 43 ]. Elevated IL-17 A levels in children with ASD provide additional support for the involvement of inflammatory processes in the pathogenesis of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-based abnormalities include abnormalities in monoamine neurotransmitter production, imbalances in the excitatory to inhibitory balance, and epilepsy [3][4][5]. Systemic abnormalities including immune dysfunction, oxidative stress and metabolic disorders may also be linked with ASD [6][7][8][9][10]. These abnormalities can interact to negatively reinforce each other.…”
Section: Introductionmentioning
confidence: 99%